(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Effective language teaching goes beyond the delivery of content—it includes how lessons begin, conclude, and are structured overall. This article explores alternative and student-centered approaches to starting and ending lessons, and innovative methods of designing syllabi that involve learners in meaningful ways. Drawing on practical classroom strategies, teacher reflections, and academic research, it presents flexible, engaging, and inclusive techniques that can be applied in various contexts. These approaches enhance student motivation, autonomy, and retention by focusing on the learning process, not just the outcomes.